Characterization of Yersinia pestis Interactions with Human Neutrophils In vitro - Dudte, Sophia C.; Hinnebusch, B. Joseph; Shannon, Jeffrey G. (Frontiers in Cellular and Infection Microbiology, 2017)
Yersinia pestis is a gram-negative, zoonotic, bacterial pathogen, and the causative agent of plague. The bubonic form of plague occurs subsequent to deposition of bacteria in the skin by the bite of an infected flea. Neutrophils are recruited to the site of infection within the first few hours and interactions between neutrophils and Y. pestis have been demonstrated in vivo. In contrast to macrophages, neutrophils have been considered non-permissive to Y. pestis intracellular survival. Several studies have shown killing of the vast majority of Y. pestis ingested by human neutrophils. However, survival of 10–15% of Y. pestis after phagocytosis by neutrophils is consistently observed. Furthermore, these surviving bacteria eventually replicate within and escape from the neutrophils. We set out to further characterize the interactions between Y. pestis and human neutrophils by (1) determining the effects of known Y. pestis virulence factors on bacterial survival after uptake by neutrophils, (2) examining the mechanisms employed by the neutrophil to kill the majority of intracellular Y. pestis, (3) determining the activation phenotype of Y. pestis-infected neutrophils, and (4) characterizing the Y. pestis-containing phagosome in neutrophils. We infected human neutrophils in vitro with Y. pestis and assayed bacterial survival and uptake. Deletion of the caf1 gene responsible for F1 capsule production resulted in significantly increased uptake of Y. pestis. Surprisingly, while the two-component regulator PhoPQ system is important for survival of Y. pestis within neutrophils, pre-induction of this system prior to infection did not increase bacterial survival. We used an IPTG-inducible mCherry construct to distinguish viable from non-viable intracellular bacteria and determined the association of the Y. pestis-containing phagosome with neutrophil NADPH-oxidase and markers of primary, secondary and tertiary granules. Additionally, we show that inhibition of reactive oxygen species (ROS) production or Src family kinases increased survival of intracellular bacteria indicating that both ROS and granule-phagosome fusion contribute to neutrophil killing of Y. pestis. The data presented here further our understanding of the Y. pestis neutrophil interactions and suggest the existence of still unknown virulence factors involved in Y. pestis survival within neutrophils.